2023
DOI: 10.1039/d2cc06999g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical C(sp3)–H functionalization of ethersviahydrogen-atom transfer by means of cathodic reduction

Abstract: The chemo- and stereoselective electrochemical allylation (and alkylation) of ethers is presented via a C(sp3)-H activation event and subsequent condensation on electron-poor olefins, such as Morita-Baylis-Hillman derivatives (MBH). The electrosynthetic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In 2023, Bandini's group reported a novel scheme for the electrochemically induced C(sp 3 )À H ether functionalization (Scheme 37). [46] This approach enables the electrochemical C(sp 3 )À H ether compound functionalization for the first time via a HAT reaction using cathodic reduction. The reaction achieves C(sp 3 )À H functionalization of different types of ether molecules via a redox-activated carbonate as a HAT promoter, which functionalizes the CÀ H bond in the ether molecule to an allyl group by means of HAT.…”
Section: Discussionmentioning
confidence: 99%
“…In 2023, Bandini's group reported a novel scheme for the electrochemically induced C(sp 3 )À H ether functionalization (Scheme 37). [46] This approach enables the electrochemical C(sp 3 )À H ether compound functionalization for the first time via a HAT reaction using cathodic reduction. The reaction achieves C(sp 3 )À H functionalization of different types of ether molecules via a redox-activated carbonate as a HAT promoter, which functionalizes the CÀ H bond in the ether molecule to an allyl group by means of HAT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current results and precedent literature, , the plausible mechanism for this electroreductive C­(sp 3 )–H arylation protocol was proposed (Scheme b). Cathodic reduction of the terephthalonitrile 2a occurs and generates the terephthalonitrile radical anion intermediate A . The intermediate A may serve two roles: One role as a mediator initiates single electron reduction of the ether 1a or the Zn 2+ -coordinated ether intermediate B to form the ether radical anion intermediate C , followed by decomposition of the iodine ions and HAT to afford the alkyl radical intermediate E and the other role as an arylating reagent that undergoes radical–radical coupling with the intermediate E to produce the anion intermediate F . Finally, decyanation of intermediate F delivers the desired product 3aa .…”
mentioning
confidence: 89%
“…In recent years, atom transfer, especially involving hydrogen atom transfer (HAT) and halogen atom transfer (XAT), has been renewed as a powerful technology by using a photochemical or electrochemical catalysis for the functionalization of C–X and C–H bonds via single-electron transfer (SET) pathways. We envisioned that using an entropically favored intramolecular HAT strategy combined with an XAT mechanism would enable site selective formation of the α-C­(sp 3 )-centered radicals, thus leading to highly regioselective α-(hetero)­arylation of unsymmetrical ethers.…”
mentioning
confidence: 99%
“…In 2023, Fermi, Bertuzzi, Bandini, and co-workers reported the electrochemical C(sp 3 )–H functionalization of ethers via hydrogen atom transfer (Scheme 17). 31 Under optimized electrochemical reaction conditions, it was found that a variety of ethers could undergo selective allylation using Morita–Baylis–Hillman acetates in the presence of redox active carbonates. A sacrificial zinc anode was used in combination with a graphite cathode, with either constant voltage electrolysis (CVE) or constant current electrolysis (CCE) employed depending upon the reagents used.…”
Section: Hydrogen Atom Transfer Processesmentioning
confidence: 99%